Edukasi dan Pelatihan Teknik Budidaya Hidroponik pada Kelompok Siswa SMA Negeri 1 Guru Lombok, Kecamatan Kalawat, Minahasa Utara - Najoan, Jemmy; Paulus, Jeanne Martje; Demmassabu, Langimanapa Sofia (Jurnal Lentera: Penelitian dan Pengabdian Masyarakat, 2026)
Hydroponic cultivation techniques are a solution to limited land in urban areas. Hidroponic cultivation has advantages, including: greater crop production per unit area, faster plant growth, more efficient use of fertilizer, more efficient use of water, less labour, cleaner work environment, easy to control water, nutrients, and pH, easy to control pests and plant diseases, and not dependent on climate and weather conditions. PKM partners are a group of students from SMAN a Guru Lombok , Kalawat, North Minahasa. The science and technologythat will be applied to the partner group are: (1) introduction to an environmentally friendly urban farming system with hydroponic cultivation to meet house hold foods needs, (2) training in hydroponic cultivation techniques, practiced directly: how to use a pH meter to measure the acidity level of nutrient solutions, how to use TDS meter to measure the concentration of AB mix nutrient solution, how to prepare ABmix nutrient, sowing vegetable seed, transplanting vegetable seedlingson hydroponic racks, plant maintenance, harvesting, and post harvesting including packaging hydroponic vegetable products ready for marketing. The implemantition methode include: (1) counseling and training in hydroponic cultivation techniques; (2) creation of a demonstration plot by preparing hydroponic tanks and installations; (3) mentoring partner groups in implementing hydroponic vegetable cultivation activities from seedbed preparation to harvest and post harvest; (4) monitoring and evaluation of PKM activities to determine whether the training activities can be implemented by partner groups in subsequent plantings. PKM activities results: (1) increased theoritical understanding by a group of students from SMA Negeri Guru Lombok, Kqaalawat regarding the basic concept of urban farming and the working principles of hydroponic systems; (2) improved practical skill, equipping students with practical skills ranging form correct seed sowing techniques, AB mix nutrient formulations, installation, instalation assembly, and daily maintenance techniques; (3) fostering motivation and entrepreneurship spirit (Agropreneurshid) among yong people utilizing modern agricultural technology at home and shool levels. The outputs PKM activity include: (1) YouTube publications; (2) publication of an ISSN-Certified community service Journal.